FEED INTAKE, ABSORPTION, CONVERSION AND GROWTH OF FRY AND FINGERLINGS OF ROHU LABEO ROHITA (HAMILTON) - Singh, B N; Sinha, V R P; Chakraborty, D P (Indian Journal of Fisheries, 2011)
A mixturre of fishmeal plus groundnut oilcake plus wheat bran and yeast in a ratio 25 : 65 : 5(10) : 5, having a protein content of about 45%, was found to bs better utilized and gave significantly tetter conversion rate than the conventional feed, a mixture of gixjundinut oilcake and wheat bran in the proportioci 1 : 1, indicating that the bran portion of the conventional feed may be succesrfuHy reduced and flsbmeal added to its place for obtaining significantly higheir rate of growth. The yeast increased the aoceptibility and conversion of feeds. The effects of oxygen content in water on rates of feed intake, absorption and growth are also discussed.